P445 Anxiety about HIV and use of HIV pre-exposure prophylaxis among gay and bisexual men. (14th July 2019) - Prestage, Garrett; Keen, Phillip; Hammoud, Mohamed; Bourne, Adam; Bavinton, Benjamin; Holt, Martin; Vaccher, Stefanie; Saxton, Peter; Maher, Lisa; Haire, Bridget; Jin, Fengyi
Abstract : Background: Many gay and bisexual men (GBM) experience anxiety about HIV, particularly in relation to sex. Use of HIV pre-exposure prophylaxis (PrEP) as an HIV prevention strategy may affect levels of HIV-related anxiety among GBM. Methods: Flux is an Australian online prospective study of GBM enrolled between 2014 and 2018. We measured anxiety using the generalized anxiety disorder assessment (GAD7) scale and a newly developed HIV anxiety scale developed using Principal Components Analysis. We assessed behavioral eligibility for PrEP based on Australian PrEP clinical prescribing guidelines. We used multivariate logistic regression to assess associations between use of PrEP and both GAD7 and HIV-specific anxiety. Results: Among 1574 men who completed the HIV anxiety scale, mean age was 37.2 years (SD 13.13). Men aged 25 years or younger had higher HIV anxiety scores than their older counterparts (p<0.001). Men who reported condomless anal intercourse with casual partners (CLAIC) scored higher on HIV anxiety than men who reported no CLAIC (p=0.033). Among 1168 men who were not eligible for PrEP according to Australian guidelines, neither GAD7 nor HIV anxiety was independently associated with PrEP use. Among 406 PrEP-eligible men (26.2%), PrEP users scored lower on GAD7 than did non-users (OR=0.95; 95%CI: 0.92–0.99) and PrEP use was independently associated with lower HIV anxiety (aOR=0.91; 95%CI: 0.85–0.97). Conclusion: Among men who were eligible for PrEP, its use was independently associated with lower levels of anxiety in general, and of HIV anxiety specifically. PrEP use may help reduce anxiety among men who are at risk of HIV and may therefore offer perceived benefits in addition to avoiding HIV infection. This perceived benefit may be an important consideration in recommendations for PrEP use. Disclosure: No significant relationships.